The Impact of Comorbidity on Rehabilitation Outcome After Ischemic Stroke - Dušica Simić-Panić; Ksenija Bošković; Marija Milićević; Tamara Rabi Žikić; Mina Cvjetković Bošnjak; Snežana Tomašević-Todorović; Mirjana Jovićević (Acta Clinica Croatica, 2018)
Comorbidity decreases survival but it still remains unknown to what extent functional recovery after ischemic stroke is affected. The aim of this research was to determine the prevalence of the most common comorbidities in patients with ischemic stroke and to examine their predictive value on the functional status and recovery. In order to obtain relevant information for this research, we conducted a prospective study over a two-year period. It included patients with acute/subacute ischemic stroke who had inhospital rehabilitation treatment in our institution. Functional status of the patients was evaluated by the following three aspects at the beginning and at the end of rehabilitation treatment: Rivermead Mobility Index was used for mobility, Barthel Index for independence in activities of daily living, and modified Rankin Scale for total disability. Modified Charlston Comorbidity Index was used to assess comorbidity. Multivariate analysis was applied to evaluate the impact of recorded comorbidities on the patient functional outcome. Independent predictors of rehabilitation success in our study were the value of modified Charlston Comorbidity Index, atrial fibrillation and myocardial infarction. Our study demonstrated that patients with more comorbidities had worse functional outcome after stroke, so it is important to consider the comorbidity status when planning the rehabilitation treatment.